Healthcare professionals view on provision preconception care for diabetes childbearing women - Omowunmi, Asafa Kafayat; Muda, Siti Mariam (International Islamic University Malaysia, 2019)
chronic hyperglycemia, from defects in insulin secretion, insulin action, or both. Diabetes is a growing public health concern. Both developed and developing countries are affected by the estimated increase for several decades. The national and international recommendation had been that women of reproductive age should offer diabetes preconception care prior conceive. The purpose of this review is to identify any study been carried out on the view of healthcare professionals on preconception care for diabetes childbearing women in different countries. The methodology includes a systematic search of databases from PubMed, MEDLINE, Wiley Online Library, Science Direct, Scopus and Pro-quest, discussed research studies that analysed healthcare professionals views on preconception care, with thirteen studies chosen for this review. Results represent both qualitative and mixed methods published between 2014-2019. Themes generated explained healthcare professionals’ views on preconception care. The concept of preconception care is beneficiary and important for diabetes women. Meanwhile, professionals’ role ambiguity might hinder the care, but primarily midwives should be responsible for providing the provision. However, some professionals perceived barriers were limited awareness and inadequate knowledge regarding diabetes preconception care as this aspect was not properly taught during professional training. In conclusion, effective preconception care is a primary prevention and has proven to reduce adverse pregnancy outcomes related to diabetes and improve glycemic control with great improvement on the intake of preconception folic acid supplement in developed countries. However, the reality to provide the proper provision of preconception care into regular consultation requires further investigation on how to achieve proper integration considering in-course professional training, time and incentives for further study.